Dropouts Need Not Apply? The Minimum Wage and Skill Upgrading - Clemens, Jeffrey; Kahn, Lisa B.; Meer, Jonathan (Journal of Labor Economics, 2021)
We explore whether minimum wage increases result in substitution from lower-skilled to slightly higher-skilled labor. Using 2011–16 American Community Survey (ACS) data, we show that workers employed in low-wage occupations are older and more likely to have a high school diploma following recent statutory minimum wage increases. To better understand the role of firms, we examine the Burning Glass vacancy data. We find increases in a high school diploma requirement following minimum wage hikes, consistent with our ACS evidence on stocks of employed workers. We see substantial adjustments to requirements both within and across firms.